Lighting System Design Based on SNI 6197-2011 and Software-Based Design DIALux Evo 9.2 (Case Study: Pekanbaru High School of Technology) - Mulya Feri; Chairul Gagarin Irianto (ELKHA : Jurnal Teknik Elektro, 2022)
Lighting is one of the important factors in a room design. The intensity of lighting that does not meet the standards can affect eye health and work activities. In this study, measurements of the lighting intensity were carried out at Pekanbaru College of Technology (STTP) i.e., in classroom 01A and library. Lumen method is one of the calculation methods to determine the number of luminaires required to improve the lighting quality in the room. For the lighting in classroom 01A, the mathematical calculations result in 363.23 lux while the DIALux evo 9.2 software obtained 375 lux. There is 3.1% difference in these results This might occur because the condition of the room, supporting equipment, and color has an influence on the results of calculations and the spread of light, while the effect of color is not considered. However, in calculations using DIALux evo 9.2 software, surface color has an influence on the results obtained.by changing the specifications of the lamp using the type of LED lamp. The lighting standard to improve the lighting system refers to SNI 6197:2011.